2006
DOI: 10.1002/hipo.20172
|View full text |Cite
|
Sign up to set email alerts
|

Increased estrogen receptor β expression correlates with decreased spine formation in the rat hippocampus

Abstract: Estrogens play an important role in the brain function acting through two receptor types, ERalpha and ERbeta, both well-recognized as transcription factors. In this study, we investigated the ERbeta mRNA and protein levels in the rat hippocampus by using two in vivo models that are known to affect synapse formation. Natural estrous-proestrous cycle was used as a model in which a marked decrease in the density of hippocampal synapses was previously observed between proestrus and estrus. We have found that ERbet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
44
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 70 publications
0
44
0
1
Order By: Relevance
“…The role of estrogen and its receptors in changes of dendritic spines is not clear. Srivastava et al have shown that WAY-200070, an ERβ agonist, increased spine density (38), whereas Szymczak et al (39) found that estrogen induces spine density but that overexpression of ERβ in hippocampal neurons from embryonic rat brains by means of gene transfection, opposed the induction by estrogen. The discrepancies between the different results from these studies may be due to different treatment methods, models, and duration of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The role of estrogen and its receptors in changes of dendritic spines is not clear. Srivastava et al have shown that WAY-200070, an ERβ agonist, increased spine density (38), whereas Szymczak et al (39) found that estrogen induces spine density but that overexpression of ERβ in hippocampal neurons from embryonic rat brains by means of gene transfection, opposed the induction by estrogen. The discrepancies between the different results from these studies may be due to different treatment methods, models, and duration of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…ERb isoform has been involved in the modulation of spine dendritic content in the hippocampus as a low level of its expression correlates with the estradiolinduced spine increase in pyramidal neurons (Szymczak et al, 2006). In the same line, ERb knockout mice are unable to learn a spatial task (Rissman et al, 2002;Liu et al, 2008), while the administration of an agonist of these receptors, but not an ERa agonist, improves the performance of mice in hippocampus-dependent memory tasks (Liu et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…11,55 reduction of cytokines levels, T cells, and macrophages; 49,50,53 and downregulation of both astroglial proliferation and activation of astrocytes.…”
mentioning
confidence: 99%
“…Many studies have reported a primary role for ERa as a regulator of the antiinflammatory properties of estradiol, including the antiinflammatory and neuroprotective activity of estradiol, 3,9,55 neuroprotection after ischemia, 12,44,50 inhibition of microglial activation, and inhibition of high MMP-9 levels. 54 In addition, a growing number of studies have reported antiinflammatory roles for ERb, such as neuroprotection after ischemia, 1,8,57 inhibition of microglial activity, 4 suppression of transcription, and decreased levels of IL-1b, IL-6, TNFa, and chemokine CCL2.…”
mentioning
confidence: 99%